Parasites and Infection (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Parasitism is an ecological relationship in which an organism, a parasite, lives inside or on another organism, the host, with the former depending on the latter to acquire shelter and essential nutrients, and survive. Thus, it is a relationship that benefits the parasite at the expense of the host, but does not necessarily result in the host's death. In humans, parasitic diseases hamper development and still cause high mortality, especially in children in developing countries. Parasitic infections in poultry, cattle, or swine, for example, are responsible for economic losses in livestock. Indeed, the proximity to infected animals puts humans at risk of zoonosis. Herein are thirteen publications covering basic biology, genetics, new diagnostic tools and treatments, control strategies, disease epidemiology, and the pathogenesis of protozoan and helminth parasites of medical importance.